1977
DOI: 10.1002/1097-0142(197709)40:3<1246::aid-cncr2820400340>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of bladder cancer.A second look

Abstract: A case-control study among 574 male and 158 female bladder cancer patients and equal numbers of matched controls w a s conducted between 1969 and 1974 in 17 hospitals in six United States cities. We determined that cigarette smokers of both sexes were at higher relative risk than nonsmokers. Cigarette smoking was responsible for about one-half of male and one-third of female bladder cancer. There was an excess of bladder cancer patients with some previous occupational exposure, such as rubber, chemicals, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
3
7

Year Published

1978
1978
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(70 citation statements)
references
References 59 publications
8
52
3
7
Order By: Relevance
“…35 Schistosomiasis is common in Gizan Province due to the relative abundance of free-lying water and widespread agriculture and this may be responsible for the large number of bladder SCCs seen in this region. A consistent relationship has been demonstrated between bladder cancer and cigarette smoking 36 but the high incidence in Gizan Province occurs with a historically low incidence of cigarette smoking.…”
Section: Discussionmentioning
confidence: 61%
“…35 Schistosomiasis is common in Gizan Province due to the relative abundance of free-lying water and widespread agriculture and this may be responsible for the large number of bladder SCCs seen in this region. A consistent relationship has been demonstrated between bladder cancer and cigarette smoking 36 but the high incidence in Gizan Province occurs with a historically low incidence of cigarette smoking.…”
Section: Discussionmentioning
confidence: 61%
“…Likewise, although there was significant association between liquor consumption and incidence of bladder cancer, this was totally the result of one outlying data point. Since neither casecontrol nor correlation studies have previously found bladder cancer to be associated with liquor consumption (Wynder & Goldsmith, 1977) this finding is probably spurious.…”
Section: Discussionmentioning
confidence: 86%
“…The most common risk factors for bladder cancer are cigarette smoking, exposure to industrial carcinogens (aromatic amines), high levels of arsenic intake and diet [150]. Oxidative stress critically contributes to the development of bladder cancer [151].…”
Section: Bladder Cancermentioning
confidence: 99%